Identifikasi Miskonsepsi Siswa Dengan Three Tier Essay Test Item Pada Materi Hukum Newton Di SMA Negeri 1 Pademawu - Ummi Farihah; Arin Wildani (Wacana Didaktika, 2018)
This research is based on students' unappropriate concept during the learning process with concepts from physicists. The incompatibility of understanding the concept is often referred to as misconception. Students' misconceptions need to be identified and then minimized so that the learning process of students goes well. This study aims to determine the profile of physical misconceptions by using three tier essays on the material of Newton's law. This research is descriptive research with quantitative and qualitative approaches. The subjects in this study were students of class X IPA 2 which consints 31 students with sample selection techniques using Random Sampling. The data collection techniques used in the form of tests and interviews. Data analysis of this misconception is carried out quantitatively and qualitatively. Analysis of quantitative data to be analyzed is the percentage of scientific knowledge, misconceptions, no self-confidence and lack of knowledge. While qualitative data analysis by processing data from research results in the form of interview recordings presented in the form of descriptive data exposure. Based on data analysis, obtained from the 6 questions tested revealed misconceptions in students with a total of 9 misconceptions profiles, so that it can be concluded that in SMAN 1 Pademawu there were misconceptions in the material of Newton's law. Keywords: Misconception, three tier essay, Newton’s law Abstrak: Penelitian ini berlatar belakang ketidaksesuaian konsep siswa pada saat proses pembelajaran dengan konsep dari para ahli fisika. Ketidaksesuaian pemahaman konsep tersebut seringkali disebut sebagai miskonsepsi. Miskonsepsi siswa perlu diidentifikasi dan selanjutnya diminimalisir agar proses belajar siswa berjalan dengan baik. Penelitian ini bertujuan untuk mengetahui profil miskonsepsi fisika dengan menggunakan three tier essay pada materi hukum Newton. Penelitian ini merupakan penelitian deksriptif dengan pendekatan kuantitatif dan kualitatif. Subjek dalam penelitian ini yaitu siswa kelas X IPA 2 yang berjumlah 31 siswa dengan teknik pemilihan sampel menggunakan Random Sampling. Adapun teknik pengumpulan data yang digunakan berupa tes dan wawancara. Analisis data miskonsepsi ini dilakukan secara kuantitatif dan kualitatif. Analisis data kuantitatif yang akan dianalisis adalah presentase pengetahuan ilmiah, miskonsepsi, tidak ada keyakinan diri dan kurang pengetahuan. Sedangkan analisis data kualitatif dengan mengolah data dari hasil penelitian berupa rekaman wawancara yang disajikan dalam bentuk paparan data secara deskriptif. Berdasarkan analisis data, diperoleh dari 6 soal yang diujikan terungkap adanya miskonsepsi pada siswa dengan total 9 profil miskonsepsi, sehingga dapat disimpulkan bahwa di SMAN 1 Pademawu terdapat miskonsepsi pada materi hukum Newton.